ONEMATOPE BAHASA SUNDA DAN TERJEMAHANNYA DALAM BAHASA INGGRIS - Yaya Mulya Mantri (TEXTURA, 2018)
This research focuses on onomatopoeic words consisted in Sundanese poetry and it translated English. The Sundanese poetry is the anthology of Sundanese poetry: Modern Sundanese Poetry Voices from West Java in Sundanese and English compiled by Ajip Rosidi and translated by Wendy Mukherjee. This research focuses on two problems. The first is to find out the sources (of sounds) of onomatopoeic words in the anthology of Sundanese poetry. The second is to explore the differences or similarities of words sounds and sources both in Sundanese and its English translated version. From the whole analysis, it concludes that Sundanese onomatopoeic words have three sources (of sounds): things, animal, and human.